2020
DOI: 10.1021/acs.organomet.9b00779
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Imido-Transfer Reactions of Well-Defined Silica-Supported Titanium Imido Complexes Prepared via Surface Organometallic Chemistry

Abstract: We expand the series of well-defined silica-supported titanium imido complexes of general formula (SiO)­Ti­(NtBu)­X­(py) n prepared via surface organometallic chemistry in order to analyze the effect of the X ligand on their catalytic properties. Two new surface complexes, (SiO)­Ti­(NtBu)­Cl­(py)2 (2s) and (SiO)­Ti­(NtBu)­Cp­(py) (3s), have been prepared and characterized with physicochemical techniques, and their performance in oxo/imido heterometathesis and other catalytic imido-transfer reactions has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 92 publications
2
22
0
Order By: Relevance
“…While this review has concentrated on olen metathesis and demonstrated that SOMC can generate highly performant catalysts that can surpass in some cases their homogeneous analogues, one can see that this methodology can be readily transposed to related reactions, such as alkyne, 46,47,199,200 imine, 201,202 and oxo/imido 203,204 metathesis, which involve cleavage of p-bonded systems. These concepts can also be used to develop alkane metathesis reactions that involve similar elementary steps.…”
Section: Conclusion Generalizations and Perspectivesmentioning
confidence: 99%
“…While this review has concentrated on olen metathesis and demonstrated that SOMC can generate highly performant catalysts that can surpass in some cases their homogeneous analogues, one can see that this methodology can be readily transposed to related reactions, such as alkyne, 46,47,199,200 imine, 201,202 and oxo/imido 203,204 metathesis, which involve cleavage of p-bonded systems. These concepts can also be used to develop alkane metathesis reactions that involve similar elementary steps.…”
Section: Conclusion Generalizations and Perspectivesmentioning
confidence: 99%
“…85 % grafting (the typically observed value at quantitative consumption of the molecular precursor is 0.23 mmol Ti g À 1 ). [10,11] The Ti/N/C ratio 1 : 1.8 : 28.2 is higher in C than the expected value of 1 : 2 : 24. IR spectroscopy showed the disappearance of the band of isolated silanols at 3747 cm À 1 (Figure 2,b), although a broad feature observed in the region 3800-3500 cm À 1 indicated that certain amount of silanol groups remained on the surface.…”
Section: Synthesis and Grafting Of Imido Bis-aryloxide Ti(=n T Bu)(oa...mentioning
confidence: 82%
“…The most important region of the spectrum is the area of the quaternary NCMe 3 resonance (40-80 ppm) as this signal is strongly sensitive to the state of N t Bu group. [1,11] It is well-known that for Ti complexes containing =N t Bu, À NH t Bu and NH 2 t Bu ligands, this resonance usually appears at ca. 70, 60 and 50 ppm respectively (see references given in Ref.…”
Section: Synthesis and Grafting Of Imido Bis-aryloxide Ti(=n T Bu)(oa...mentioning
confidence: 99%
See 2 more Smart Citations